A Tourism e-Guide System Using Mobile Integration - Abuelrub, Emad M.; Solaiman, Hanan M. (International Journal of Interactive Mobile Technologies (iJIM), 2010)
This paper presents a tourism e-guide system via mobile integration using offloading while enjoying mobility. A user can search for new mobile services available on the website to use either remotely on the server where the services resides, or locally after downloading them to his/her mobile device and work offline without a mobile connection. Jordan Tourism e-Guide System (JTeGS) aims to help the user/tourist accessing the tourism information directly from his/her smart device, anytime and anywhere using offloading. JTeGS is a web-based electronic guide that provides the user with appropriate tourism information about Jordan and guides him/her to find the best places to party, eat out, and enjoy culture events. The system architecture and the main components of the proposed services were presented and discussed. The system has been prototyped and validated in a real-time mobile internet application scenario. The system also has been evaluated through simulations in mobile network environment. Both experimental and simulation results demonstrated the effectiveness and efficiency of the proposed system.